(untitled) (Kwasu International Journal of Educational Management and Leadership, 2026)
The study examined the relationship between Vice-chancellors’ motivational techniques and goal achievement in Universities in South-west, Nigeria. It adopted correlational research design. The population for the study consisted of 15,230 lecturers in universities in Southwest, Nigeria. Stratified sampling technique was used to obtain a sample of 1,523 respondents. Both face and content were validated by three experts and Cronbach Alpha method was adopted to ensure reliability of the instrument with the coefficient of r =0.78 and r =0.80. The questionnaire was administered to 1,523 respondents out of which 1,481 copies were retrieved from the respondents indicating 97% level of retrieval. The questionnaire titled Vice-Chancellor’s Motivational Techniques and Goal Achievement Questionnaire was used for data collection.Mean and standard deviation were used to answer research questions while Pearson product moment correlation statistics was used to test the hypothesis at 0.05 level of significance. The findings of the study revealed that vice-chancellors used motivational techniques to achieve universities’ goals x goal achievement was moderately attained x The study concluded that there was a relationship etween Vice Chancellors’ motivational techniques and goal achievements in universities in South west, Nigeria. Based on the findings, it was recommended among others, that the National Universities Commission should organize workshops, seminars, and conferences for university vice chancellors to abreast them of the latest development, enhancing their efficiency and effectiveness in discharging their responsibilities.